2017
DOI: 10.1186/s12879-017-2674-4
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Herpes Simplex Virus type-2 (HSV-2) among pregnant women who participated in a national HIV surveillance activity in Haiti

Abstract: BackgroundHerpes simplex virus type 2 (HSV-2), one the most common causes of genital ulcers, appears to increase both the risk of HIV acquisition and HIV transmission. HSV-2/HIV co-infection among pregnant women may increase the risk of perinatal transmission of HIV. This study describes rates of HSV-2 among pregnant women in Haiti and HSV-2 test performance in this population.MethodsUnlinked residual serum specimens from the 2012 National HIV and Syphilis Sentinel Surveillance Survey among pregnant women in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
6
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
2
7
6
2
Order By: Relevance
“…Our study confirmed the previous observations that the prevalence of HSV-2 increased with age and number of children. It was higher than what has been found in rural places of for example Haiti and Costa Rica where reported prevalences are 42 and 38%, respectively [22,23], and similar to prevalences in Durban, Tanzania, and a region in Brazil [19,24,25]. Our observation that HSV-2 was more prevalent in small villages compared to the small and large towns differs from what has been observed in Haiti, Tanzania and Brazil where the prevalence of HSV-2 was higher in urban compare to rural areas.…”
Section: Discussioncontrasting
confidence: 69%
“…Our study confirmed the previous observations that the prevalence of HSV-2 increased with age and number of children. It was higher than what has been found in rural places of for example Haiti and Costa Rica where reported prevalences are 42 and 38%, respectively [22,23], and similar to prevalences in Durban, Tanzania, and a region in Brazil [19,24,25]. Our observation that HSV-2 was more prevalent in small villages compared to the small and large towns differs from what has been observed in Haiti, Tanzania and Brazil where the prevalence of HSV-2 was higher in urban compare to rural areas.…”
Section: Discussioncontrasting
confidence: 69%
“…Our study confirmed the previous observations that the prevalence of HSV-2 increased with age and number of children. It was higher than what has been found in rural places of for example Haiti and Costa Rica where reported prevalences are 42% and 38%, respectively [22,23], and similar to prevalences in Durban, Tanzania, and a region in Brazil [19,24,25]. Our observation that HSV-2 was more prevalent in small villages compared to the small and large towns differs from what has been observed in Haiti, Tanzania and Brazil where the prevalence of HSV-2 was higher in urban compare to rural areas.…”
Section: Discussioncontrasting
confidence: 68%
“…Similar to Ethiopia, the overall weighted prevalence of HSV‐2 was 31.4 % in Haiti, while in Korea, Kim et al. reported an HSV‐2 prevalence of 17 % . In the United States, between 1989–2010, 53 % of pregnant women were seropositive for HSV‐1, 9 % for HSV‐2 and 15 % were seropositive for both .…”
Section: Prevalence Incidence and Burden Of The Diseasementioning
confidence: 94%